The missing girls and women of China, Hong Kong and Taiwan a sociological study of infanticide, forced prostitution, political imprisonment, "ghost brides," runaways, and thrownaways, 1900-2000s - Huang, Hua-Lun, 1962-; ebrary, Inc. (Jefferson, N.C. : McFarland & Co., 2012)
"In the past century, tens of millions of women and girls have disappeared in China, Hong Kong, and Taiwan. This sociological study explores the institutional factors contributing to the phenomenon of missing females, develops a typology for these populations, and lays a foundation for social scientists to examine lost populations in the future"--Provided by publisher.
Tables and figures -- Preface -- Introduction -- The study of missing females -- Conceptualization of missing females : a classification system -- Missing females at high risk of vanishing permanently -- Female political prisoners -- Slain baby girls -- Ghost brides -- Missing females with some chances to re-emerge -- Comfort women -- Trafficked women and girls -- Runaways/thrownaways -- Conclusion -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Missing persons -- East Asia; Missing children -- East Asia; Sex of children, Parental preferences for -- East Asia; Female infanticide -- East Asia; Women -- East Asia -- Social conditions -- 20th century; Prostitutes -- East Asia -- Social conditions -- 20th century; Women's rights -- East Asia; Electronic books